Studying the Effect of Gas Processing Plants' Waste on Human Health in Uzbekistan - Navotova Dilnoza Ibrogimovna; Azimov Azamat Faxriddin o‘g‘li (Periodica Journal, 2022)
The article analyzes the emissions of industrial enterprises in our country and the negative impact of these wastes on human health.
Keywords: fuel; hydrogen sulfide; hydrocarbon; allergy